Does induction or augmentation of labor increase the risk of postpartum hemorrhage in pregnant women with anemia? A multicenter prospective cohort study in India - Cheng, TS; Zahir, F; Solomi V, C; Verma, A; Rao, S; Choudhury, SS; Deka, G; Mahanta, P; Kakoty, S; Medhi, R; Chhabra, S; Rani, A; et al. (Wiley, 2024)
Objective: To investigate whether induction/augmentation of labor in pregnant women with anemia increases the risk of postpartum hemorrhage (PPH) and whether this risk varied by indications for labor induction/augmentation and by anemia severity in pregnancy. Methods: In a prospective cohort study of 9420 pregnant women from 13 hospitals across India, we measured hemoglobin concentrations at recruitment (≥28 weeks of gestation) and blood loss after childbirth during follow-up and collected clinical information about PPH. Clinical obstetric and childbirth information at both visits were extracted from medical records. Anemia severity in the third trimester was categorized using hemoglobin concentrations (no/mild anemia: hemoglobin ≥10 g/dL; moderate: hemoglobin 7 to 9.9 g/dL; severe: hemoglobin <7 g/dL), while PPH was defined based on blood loss volume (vaginal births: ≥500 mL or cesarean sections: ≥1000 mL) and clinical diagnosis. Indications for labor induction/augmentation were classified as clinically indicated and elective as per guidelines. We performed multivariable modified Poisson regression analyses to investigate the associations of anemia severity and indications for labor induction/augmentation, including their interaction, with PPH, adjusted for potential confounders. Results: PPH was associated with anemia but not with indications for labor induction/augmentation. However, there was a significant interaction between the two factors in relation to PPH (P = 0.003). Among pregnant women with severe anemia, a higher risk of PPH was associated with elective (adjusted risk ratio, 3.44 [95% confidence interval, 1.29–9.18]) but not with clinically indicated (adjusted risk ratio, 1.22 [95% confidence interval, 0.42–3.55]) labor induction/augmentation. No associations were observed among pregnant women with no/mild and moderate anemia. Conclusion: The risk of PPH is higher in women who have moderate–severe anemia in late pregnancy. Induction/augmentation of labor is generally safe for women with anemia, but it can increase the risk of PPH in women with severe anemia if performed electively.